The Reality Level of Feminism in Little Women Movie - Dinda, Putri; Dahniar, Dahniar; Tahir, Tahir (ASHLITION : Ash-Shahabah English Literature, Linguistics, & Education, 2023)
The research aims to identify and analyse the reality of feminism in the film Little Women. The problem identified in this study is to discover the signs of the level of feminism in the film Little Women. Furthermore, the research uses a qualitative descriptive method. The researcher downloaded "the Little Women" movie on the internet and watched the film. Then, the researcher selects records and takes film pictures according to the required data. Besides that, the researcher also uses John Fiske's semiotic theory to analyse the sign of reality and the sign of representation of feminism in the film Little Women. The results of this research are specific because the setting in the Little Women film strongly shows the role of women in society such as women can work, have talents that can be used to realize their dreams, have intelligence in educating children, have independence, are confident and dare to take action by ignoring the stigma attached to them. Through this character, she proves that a woman has the mind, talent, and confidence to make her way, with the intelligence to have and hone her talents.